PECAHAN SENILAI: DESAIN MEDIA KOMIK “BELAJAR BERSAMA ALIA” - Frella Anggun Silvia; Muhardila Fauziah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning media is an important aspect of the teaching and learning process in the classroom. The development of comic media has become one of the options for improving students' learning achievements. This research aims to determine the feasibility level of the comic media used in mathematics learning on the topic of fractions. The research method uses the 4D development model, which consists of four stages: Define, Design, Development, and Dissemination. The eligibility level is determined by measuring validity using a questionnaire distributed to one media expert and two content experts. The media validity results show a score of 4.9 with a percentage of 97.6%. Meanwhile, the validation from the two content experts shows a score of 4.3 with a percentage of 87.5%. Therefore, it can be concluded that the comic media "Learning Together with Alia" for teaching mathematics on the topic of fractions is suitable for trial with fourth-grade elementary school students.